Innovative Product Development from LDPE Waste using the Fusing Interlock Technique: A Material Driven Design Study Case - Gumulya, Devanny; Halim, Claresta Yuliana (Proceeding of International Joint Conference on UNESA, 2024)
In response to the escalating plastic waste issue in Indonesia, intensified by a lack of public knowledge on waste management, this research focuses on repurposing LDPE plastic waste collected from laundry service using the plastic fusing interlock technique. Employing a material-driven design method with research through design approach where design process is used as method of inquiry, exploring and investigating research questions through the creation of tangible prototypes from the LDPE plastic waste. The study identifies suitable recycling techniques for LDPE waste and assesses its feasibility in creating functional products. Through five experimental trials, the research establishes that layer-by-layer fusion is the most effective method, and cutting the fused plastic with a pond knife yields strong and versatile results. The interlocking modules produced through this technique provide flexibility for diverse configurations, offering myriad possibilities for product creation. The study concludes that the fusing interlock technique makes LDPE waste repurposing accessible and cost-effective, eliminating size limitations and enhancing product durability. The experiments utilized approximately 450 sheets of LDPE plastics, showcasing the potential for sustainable production and contributing to SDG 12: Responsible Consumption and Production.